2020
DOI: 10.1371/journal.pone.0241746
|View full text |Cite|
|
Sign up to set email alerts
|

The rural-urban divide in Tanzania: Residential context and socioeconomic inequalities in maternal health care utilization

Abstract: Background Existing studies in Tanzania, based mostly on rural samples, have primarily focused on individual behaviors responsible for the lower utilization of maternal health care. Relatively less attention had been paid to inequalities in structural circumstances that contribute to reduced utilization of maternal health care. More importantly, scholarship concerning the impact of the rural-urban divide on socioeconomic disparities in the utilization of maternal health care is virtually nonexistent in Tanzani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 44 publications
3
17
0
Order By: Relevance
“…According to the HMIS data, most of the OPD services were conducted at the HC level, and most HCs/health posts are in rural areas ( Ministry of Health of Ethiopia, 2015b ). The decomposition analyses findings also support that the urban–rural gap was the key driver for the inequality, which corresponds with findings in many other low-income countries ( Langa and Bhatta, 2020 ; Okoli et al. , 2020 ; Say and Raine, 2007 ).…”
Section: Discussionsupporting
confidence: 85%
“…According to the HMIS data, most of the OPD services were conducted at the HC level, and most HCs/health posts are in rural areas ( Ministry of Health of Ethiopia, 2015b ). The decomposition analyses findings also support that the urban–rural gap was the key driver for the inequality, which corresponds with findings in many other low-income countries ( Langa and Bhatta, 2020 ; Okoli et al. , 2020 ; Say and Raine, 2007 ).…”
Section: Discussionsupporting
confidence: 85%
“…In this study, we found only 4.7%, 7.5% and 10.1% women of coastal areas accessed maternal healthcare services in terms of ANC, assisted delivery by SBA and PNC services respectively, signi cantly lower compared to those living in plains and the national average [42]. Previous research conducted in geographically adverse rural areas of Bangladesh and other countries also reported the similar ndings [43][44][45][46][47][48][49]. Researchers discussed a number of barriers of healthcare utilization at individual, community and health systems-level.…”
Section: Discussionsupporting
confidence: 75%
“…Adherence to daily supplementation may also be lower in real-world conditions than observed in trials (although palatable and MMS-integrated BEP formulations might improve adherence). Additionally, our model does not consider differential utilization of ANC services by factors such as residency (urban versus rural) or maternal age, although such differences have been documented [ 40 ]. If supplementation interventions do not reach higher risk groups such as rural and/or young mothers, our model may overestimate their impact.…”
Section: Discussionmentioning
confidence: 99%